Comparison of Outcomes of Single-Level Anterior Cervical Discectomy With Fusion and Single-Level Artificial Cervical Disc Replacement for Single-Level Cervical Degenerative Disc Disease. Issue 1 (1st January 2017) - Pandey, Praveen Kumar; Pawar, Inder; Gupta, Jyoti; Verma, Raaghav Rai
Abstract : Study Design: A single-center, prospective comparative study of prospectively collected outcomes, with a minimum 12 months follow-up. Objectives: The primary purpose of the study is to investigate the clinical, functional, and radiological outcomes of cervical total disc replacement (CTDR) in comparison with anterior cervical discectomy and fusion (ACDF) in the treatment of single-level cervical disc degenerative disease, prospectively. Summary of Background Data: CTDR has recently been an alternative to ACDF in cervical disc degenerative disease to preserve the motion at the treated level. Methods: This study included 34 patients, who underwent either single-level ACDF (n = 17) or single-level CTDR (n = 17) at C3 to C7 level for cervical disc degenerative disease between July 2012 to April 2014 with a minimum of 12 months of follow-up. Results: Neck disability index, visual analog scale, and neck-arm pain score showed significant difference between the two groups at final follow-up of 12 months. Modified orthopedic association score and Nurick scale also showed the Japanese significant difference between the two groups at final follow-up of 12 months. Odom criteria were not statistically significant between the two groups at final follow-up. The changes in overall cervical sagittal angle (CSA) were significantly different between the two groups. The segmental angle (SA) was maintained at a significantly higher value in the CTDR group than in the ACDF group during the follow-up period ( P < 0.05). The range of motion of the cervical spine and the treated level was well maintained and improved in the CTDR group as compared with ACDF group and showed extremely statistically significant difference between the two groups. Conclusion: CTDR was found to be a safe, effective, better, and efficient alternative to the traditional ACDF. CTDR using Prestige LP cervical disc provided a statistically significant clinical, functional, and radiological outcomes between the two groups after 1-year follow-up. Level of Evidence: 2